The shadow land ebook A novel. - Kostova, Elizabeth (2017)
From the #1 bestselling author of The Historian comes a mesmerizing novel that spans the past and the present—and unearths the troubled history of a gorgeous but haunted country. A young American woman, Alexandra Boyd, has traveled to Sofia, Bulgaria, hoping that life abroad will salve the wounds left by the loss of her beloved brother. Soon after arriving in this elegant East European city, however, she helps an elderly couple into a taxi—and realizes too late that she has accidentally kept one of their bags. Inside she finds an ornately carved wooden box engraved with a name: Stoyan Lazarov. Raising the hinged lid, she discovers that she is holding an urn filled with human ashes. As Alexandra sets out to locate the family and return this precious item, she will first have to uncover the secrets of a talented musician who was shattered by political oppression—and she will find out all too quickly that this knowledge is fraught with its own danger. Elizabeth Kostova’s new novel is a tale of immense scope that delves into the horrors of a century and traverses the culture and landscape of this mysterious country. Suspenseful and beautifully written, it explores the power of stories, the pull of the past, and the hope and meaning that can sometimes be found in the aftermath of loss. Praise for The Shadow Land “A compelling and complex mystery, strong storytelling, and lyrical writing combine for an engrossing read.” —Publishers Weekly “In The Shadow Land, Elizabeth Kostova, a master storyteller, brings vividly to life an unfamiliar country—Bulgaria—and a painful history that feels particularly relevant now. You won’t want to put down this remarkable book.” —Claire Messud, author of The Woman Upstairs “In this brilliant work, what appears at first a minor mystery quickly becomes emblematic of a whole country’s hidden history. Lyrical and compelling, The Shadow Land proves a profound meditation on how evil is inflicted, endured, and, through courage and compassion, defeated. Elizabeth Kostova’s third novel clearly establishes her as one of America’s finest writers.” —Ron Rash, author of The Risen